Transcranial direct current stimulation of the right anterior temporal lobe changes interpersonal neural synchronization and shared mental processes - Long, Yuhang; Zhong, Miao; Aili, Ruhuiya; Zhang, Huan; Fang, Xiaoyi; Lu, Chunming (Brain stimulation, 2023)
Previous studies have shown that interpersonal neural synchronization (INS) is a ubiquitous phenomenon between individuals, and recent studies have further demonstrated close associations between INS and shared external sensorimotor input and/or internal mental processes within a dyad. However, most previous studies have employed an observational approach to describe the behavior-INS correlation, leading to difficulties in causally disentangling the relationship among INS, external sensorimotor input and the internal mental process. The present study aimed to directly change the level of INS through anodal transcranial direct current stimulation (tDCS) to test whether the change in INS would directly impact the internal mental process (Hypothesis 1) or indirectly through external sensorimotor input; the interaction behaviors were also changed (Hypothesis 2) or not (Hypothesis 3). Thirty pairs of romantically involved heterosexual couples were recruited for a within-subjects design. Three conditions were assessed: a true stimulation condition with 20-min anodal high-definition tDCS to the right anterior temporal lobe (rATL) of women before they communicated with their partners, a sham stimulation condition and a control brain region stimulation condition. The comparison between the true and sham or control brain region conditions allows us to detect the true effect of brain stimulation on INS. Functional near-infrared spectroscopy (fNIRS) hyperscanning was used to simultaneously collect dyadic participants' hemodynamic signals during communication. INS, empathy, and interaction behaviors were examined and compared among different stimulation conditions. True brain stimulation significantly decreased INS between the rATL of the women and sensorimotor cortex (SMC) of the men compared to the sham stimulation condition (t(27.8) = −2.821, P = 0.009, d = 0.714) and control brain region stimulation condition (t(27.2) = −2.606, P = 0.015, d = 0.664) during communication. It also significantly decreased the level of emotional empathy (F(2,145) = 6.893, P = 0.001) but did not change sensorimotor processes, such as verbal or nonverbal interaction behaviors. However, nonverbal behaviors mediated the relationship between the changes in INS and emotional empathy (lower limit confidence interval = 0.01, upper limit confidence interval = 2.66). These findings support the third hypothesis, suggesting that INS is associated with the shared internal mental process indirectly via the sensorimotor process, but the sensorimotor process itself does not covary with the INS and the associated internal mental process. These results provide new insight into the hierarchical architecture of dual-brain function from a bottom-up perspective. •Anodal tDCS on one individual changed neural synchronization between individuals.•Anodal tDCS on one individual changed empathy shared by two individuals.•Anodal tDCS on one individual didn't change interaction behaviors.•Nonverbal but not verbal behaviors mediated the change in brain and empathy.•Our findings support the hierarchical architecture of the dual-brain function.